2005
DOI: 10.1038/sj.bjc.6602818
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II study of oxaliplatin when added to 5-fluorouracil and leucovorin and pelvic radiation in locally advanced rectal cancer: a Colorectal Clinical Oncology Group (CCOG) study

Abstract: The purpose of this study was to evaluate the maximum tolerated dose (MTD) and recommended dose of oxaliplatin given synchronously with 5-fluorouracil (5FU), leucovorin (LV) and preoperative pelvic radiation for primary unresectable, locally advanced, rectal cancer. Preoperative pelvic radiotherapy using a three-or four-field technique and megavoltage photons comprised 45 Gy given in 25 fractions, 1.8 Gy per fraction, and delivered with escalating doses of oxaliplatin in combination with low-dose LV and 5FU. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 49 publications
2
13
1
1
Order By: Relevance
“…Indeed, several recent phase I -II trials have explored the activity of a combination of OXA and fluoropyrimidines (i.v. FU or oral capecitabine) during preoperative pelvic RT (Gerard et al, 2003;Rodel et al, 2003;Aschele et al, 2005;Sebag-Montefiore et al, 2005). Although all these trials have demonstrated the feasibility of such combinations, we would underline that the reported pCR rates (ranging between 7 and 28%) were clearly lower than that achieved in our study.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Indeed, several recent phase I -II trials have explored the activity of a combination of OXA and fluoropyrimidines (i.v. FU or oral capecitabine) during preoperative pelvic RT (Gerard et al, 2003;Rodel et al, 2003;Aschele et al, 2005;Sebag-Montefiore et al, 2005). Although all these trials have demonstrated the feasibility of such combinations, we would underline that the reported pCR rates (ranging between 7 and 28%) were clearly lower than that achieved in our study.…”
Section: Discussioncontrasting
confidence: 52%
“…Furthermore, the addition of OXA to a biweekly regimen of RTX and FU/FA proved manageable and active in heavily pretreated patients (Comella et al, 2002). Recently, several investigators have reported encouraging results with the addition of OXA to fluoropyrimidines during pelvic preoperative radiotherapy in LARC (Gerard et al, 2003;Rodel et al, 2003;Gambacorta et al, 2004a;Aschele et al, 2005;Sebag-Montefiore et al, 2005). For all these reasons, the combination of OXA, RTX and FU/FA with pelvic RT represents an attractive perspective in the preoperative setting of LARC.…”
mentioning
confidence: 99%
“…In colon cancer, the addition of oxaliplatin to 5-FU as adjuvant therapy after curative resection of stage II/III disease resulted in signifi cant improvement in disease-free survival (P = 0.0002) [34]. The tolerability of oxaliplatin added to 5-FU with concomitant radiotherapy in rectal cancer was established in the Lyon R 97-03 phase 1 trial in 2001 [35] and the CCOG study [36]. With weekly oxaliplatin (60 mg/m 2 ) added to continuous infusion 5-FU (225 mg/m 2 per day) and radiotherapy (1.8 Gy over 28 fractions for a total dose of 50.4 Gy) preoperatively in patients with recurrent or locally advanced (cT3-4 and/or N+) adenocarcinomas of the mid-low rectum, Aschele et al [37] found an impressive 21 of 24 patients (84%) with tumor downstaging and 7 of 24 patients (28%) with pathologic complete responses.…”
Section: Oxaliplatin In Addition To 5-fu-based Adjuvant and Neoadjuvamentioning
confidence: 97%
“…Combinations of two drugs (capecitabine and oxaliplatin; protracted venous infusions of 5-FU plus capecitabine; 5-FU/leucovorin plus capecitabine; 5-FU/leucovorin plus irinotecan), in combination with preoperative RT, have been tested in numerous phase 1/2 studies [15][16][17]. Results have shown good tolerability profiles, and the combinations have appeared to significantly increase R0 resection and tumor sterilization rates.…”
Section: Increasing the Effects Of Preoperative Crtmentioning
confidence: 98%